2008
DOI: 10.1097/aco.0b013e3283007b91
|View full text |Cite
|
Sign up to set email alerts
|

What limits for acute care in the elderly?

Abstract: Aging implies many biological modifications at molecular, cellular, organic levels as well as of the behavior. Some aspects of these processes and their consequences on health are described. The frailty concept is detailed, and its potential interest explained. We conclude that the measurement of aging phenomenon, including the frailty index, may help us to better assess the true health and the required therapeutics of elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…First, most models did not include elderly-specific factors (e.g. premorbid cognitive and functional status or co-morbidity), although there is increasing evidence that in elderly patients not age per se, but elderly-specific factors are predictive of mortality [8][9][10][11][12][13]. Useful instruments to measure these include the Katz [29] or Barthel [30] activities of daily living (ADL) index, the informant questionnaire on cognitive decline in the elderly, short form (IQCODE-sf) [31], and the Charlson co-morbidity index [32], although these may be hard to collect accurately for all patients, especially in an ICU environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most models did not include elderly-specific factors (e.g. premorbid cognitive and functional status or co-morbidity), although there is increasing evidence that in elderly patients not age per se, but elderly-specific factors are predictive of mortality [8][9][10][11][12][13]. Useful instruments to measure these include the Katz [29] or Barthel [30] activities of daily living (ADL) index, the informant questionnaire on cognitive decline in the elderly, short form (IQCODE-sf) [31], and the Charlson co-morbidity index [32], although these may be hard to collect accurately for all patients, especially in an ICU environment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that in elderly people not age per se, but other factors related to old age are predictive of mortality, including diagnosis, co-morbidity, and pre-morbid cognitive and functional status [8][9][10][11][12][13]. Although general models use age as a proxy of these factors, they may not sufficiently correct for them as calendar age and biological age diverge at older age.…”
mentioning
confidence: 99%
“…The 16-bed specialized Geriatric ICU, established in 2007, provides critical care for older patients with serious conditions. It addresses the challenges of providing care, especially to senior military officials, in a cultural expectation that filial piety is often best demonstrated by “doing everything” without regard to a patient’s age, prior level of function, or potential outcomes ( 13 ). Over 500 patients are admitted each year, chiefly for ventilation and pressor support.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, intensive care units (ICUs) are challenged to understand which older adults are most likely to benefit ( 8 , 9 , 12 ). In these circumstances, considering frailty might help ( 1 , 3 , 4 , 9 , 13 ). Typically, ICUs employ several prognostic scores, focusing on acute episodes, consciousness, vital signs, and disease severity on admission.…”
mentioning
confidence: 99%
“…15 Ramesh et al, having reviewed the implications of aging in surgical oncology, speak of prejudice and discrimination on the part of health care providers toward any person who has attained a chronological age that the social group defines as Bold. [ Therefore, an ethical dilemma exists in the clinical day when a physician is called to reach a labile counterbalance between chronological and biological age 16 and between overtreatment and undertreatment in elderly EOC patients.…”
Section: Discussionmentioning
confidence: 99%